Formal independence of regulatory agencies and Varieties of Capitalism: A case of institutional complementarity?. Issue 3 (17th March 2015) - Guardiancich, Igor; Guidi, Mattia
Abstract: The Varieties of Capitalism literature posits that national economic institutions reflect the mode of coordination of a country's market actors. Despite the importance of this claim and a rich literature on the emergence of regulatory capitalism, few studies test such prediction for Independent Regulatory Agencies (IRAs). This article connects the two fields of research by analysing the impact of economic coordination on the formal independence of IRAs. The results show that, beyond issues of credible commitment and policy stability, the collective action capacity of market actors matters. In particular, regulators in Coordinated Market Economies enjoy less independence than in Liberal Market Economies, while intermediate regimes grant IRAs the least autonomy. The policy implications are nontrivial. Similar to other macroeconomic institutions, inappropriate combinations of economic coordination and IRA independence may engender Pareto‐suboptimal regulatory solutions. In such cases, policymakers should reconsider the rules governing national regulators.